Parent-implemented augmented communication intervention and young children with Down syndrome: an exploratory report - Romski, MaryAnn; Sevcik, Rose A.; Barton-Hulsey, Andrea; Fisher, Evelyn; King, Marika; Albert, Phebe; Kaldes, Gal; Walters, Casy (Frontiers in Psychology, 2023)
Young children with Down syndrome (DS) present with speech and language impairments very early in childhood. Historically, early language intervention for children with DS included manual signs, though recently there has been an interest in the use of speech-generating devices (SGDs). In this paper, we examine the language and communication performance of young children with DS who participated in parent-implemented communication interventions that included SGDs. Specifically, we compared the functional vocabulary usage and communication interaction skills of children with DS who received augmented communication interventions (AC) that included an SGD with those children with DS who received spoken communication intervention (SC). Twenty-nine children with DS participated in this study. These children were part of one of two longitudinal RCT studies investigating the effectiveness of parent-implemented augmented communication interventions in a larger sample of children with severe communication and language impairments (N = 109). There were significant differences between children with DS in the AC and SC groups in terms of the number of functional vocabulary targets used, the proportion of functional vocabulary used, and the total vocabulary targets provided during the intervention at sessions 18 (lab) and 24 (home). Overall, the children with DS who received AC interventions were better communicators at the end of the 24-session intervention than the children who received SC intervention. The AC interventions provided them with a way to communicate via an SGD, while the children in the SC intervention were still learning to produce spoken words and did not have a conventional way to communicate. The AC interventions did not hinder the children’s speech development. It is clear that augmented communication intervention can facilitate the communication abilities of young children with DS as they are emerging spoken communicators.